(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with mid-term outcomes (mortality and limb amputation) in patients with infrapopliteal arterial occlusive disease treated by endovascular intervention at the University Medical Center Ho Chi Minh city. Methods: This was a prospective cohort observational study including 127 patients with infrapopliteal arterial stenosis or occlusion who underwent balloon angioplasty at the University Medical Center Ho Chi Minh city from January 2022 to July 2024. Results: During mid-term follow-up, underweight patients had a 3.34-fold higher risk of limb amputation compared with those with normal BMI (95% CI: 1.11-11.0; p = 0.031). Patients who died had significantly lower mean eGFR values than survivors (38.5 ± 23.4 ml/min/1,73m² vs. 69.6 ± 27.4 ml/min/1,73m²; p = 0.022). Other factors, including age, sex, and overweight/obesity, were not significant in the multivariate model. Conclusion: Poor nutritional status and impaired renal function were independent prognostic factors associated with unfavorable mid-term outcomes after endovascular intervention in patients with infrapopliteal arterial occlusive disease. Nutritional screening and renal function preservation should be emphasized in clinical practice to improve outcomes.